The Role of Work Values in Job Choice Decision - An Empirical Study - Natarajan, Commander N.K.; Nagar, Dinesh (Prabandhan: Indian Journal of Management, 2011)
Work values play an important role in employee job satisfaction and wellbeing. It also predicts organizational commitment. If values are so important, then it must also be a consideration in making a job choice by job seekers. The present study tested this empirically in 72 job seekers. The study found that the job seekers get attracted towards a particular organization which is perceived to promote values that are important to them. Further, the study also proved that values of Humanity and Vision are very important to job seekers. Thus, any organization which is perceived to be promoting these values will attract best talent in the market.